Potential pathway for recycling of the paper mill sludge compost for brick making - Goel, Gaurav; Vasić, Milica Vidak; Katiyar, Nirmal Kumar; Kirthika, S. K.; Pezo, Milada; Dinakar, P. (Elsevier, 2021)
This study's focus was to develop a potential pathway for recycling of the paper mill sludge compost (PMSC) in brick making. Composting reduces the paper mill sludge (PMS) moisture content considerably and shredding becomes easier. The addition of PMSC leads to an increase of porosities in bricks and makes them lighter, besides delivering energy to the firing process from burning organics. Lighter construction materials help minimize construction outlay by reducing labour and transportation costs and lesser expense on foundation construction. The variability in the experimental data and the brick properties were investigated for two types of soils, typical in the brick industry of India (alluvial and laterite soil), blended with PMSC in five mix ratios (0%, 5%, 10%, 15% and 20%). The samples of oven-dried bricks were fired at two different temperatures (850 and 900 ˚C) in an electrically operated muffle furnace representing typical conditions of a brick kiln. Various properties of bricks were analyzed which included linear shrinkage, bulk density, water absorption and compressive strength. Conclusions were drawn based on these properties. It was found that the addition of PMSC to the alluvial and laterite soil by up to 10% weight yield mechanical properties of fired bricks compliant with the relevant Indian and ASTM codes. Toxicity characteristic leaching procedure (TCLP) tests showed that PMSC incorporated fired bricks are safe to use in regular applications as non-load-bearing and infill walls. This study is timely in light of the European Green Deal putting focus on circular economy. Besides, it fulfils the objective of UN sustainable development goals (SDG).
Keywords: Alluvial soil; Laterite soil; Waste-to-brick; Sustainability; Recycling; Fired bricks; Paper mill sludge compost